Transforming rural China : how local institutions shape property rights in China - Chen, Chih-Jou Jay, 1966- (RoutledgeCurzon, 2004)
It is often assumed that privatization leads to profit, and that well-delineated property rights and a strong private sector will help boost economy. This book investigates the property rights in Chinese enterprises in the reform era.
Keywords: Land use, Rural -- China.; Rural development -- China.; Right of property -- China.; China -- Economic policy -- 2000-; Utilisation agricole du sol -- Chine.; Développement rural -- Chine.; Droit de propriété -- Chine.; Chine -- Politique économique -- 2000-; BUSINESS & ECONOMICS -- Real Estate -- General.; Economic policy; Land use, Rural; Right of property; Rural development; China; Plattelandsontwikkeling.; Eigendomsrecht.; Since 2000